2016
DOI: 10.1108/hcs-08-2016-0007
|View full text |Cite
|
Sign up to set email alerts
|

Housing and ageing in France and Germany: the intergenerational solution

Abstract: International audiencePurpose – In France and Germany, intergenerational housing is put forward as an option by publicauthorities. This kind of housing scheme seems like a good solution for seniors and young people, from bothan economic and a social point of view. But beyond this common philosophy, there are differences in the wayintergenerational housing is being implemented in the two countries. France mainly favours the studentseniorhome-sharing model whereas the intergenerational collaborative housing (co-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Social support was assessed through seven studies using a mixed methods design [ 12 , 35 , 45 – 49 ], including two with a comparison group [ 14 , 50 ], nine qualitative methods [ 15 , 16 , 38 – 41 , 51 53 ] and four quantitative methods [ 13 , 37 , 43 , 54 ]. Two studies with a comparison group [ 14 , 37 ] and three studies that compared the actual situation with previous situation [ 43 , 46 , 48 ] reported that social support was more evident in the cohousing model.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Social support was assessed through seven studies using a mixed methods design [ 12 , 35 , 45 – 49 ], including two with a comparison group [ 14 , 50 ], nine qualitative methods [ 15 , 16 , 38 – 41 , 51 53 ] and four quantitative methods [ 13 , 37 , 43 , 54 ]. Two studies with a comparison group [ 14 , 37 ] and three studies that compared the actual situation with previous situation [ 43 , 46 , 48 ] reported that social support was more evident in the cohousing model.…”
Section: Resultsmentioning
confidence: 99%
“…This effect could be found both in senior [ 12 , 13 , 35 , 39 , 41 , 45 , 47 50 , 52 , 54 ] and intergenerational projects [ 14 16 , 37 , 40 , 43 , 46 , 53 , 54 ]. One study found beneficial effects of social support among same-generation residents while intergenerational social support was less evident [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The availability of mutual aid and support among co-residents that would supplant or complement family or institutional support is an attractive feature of this kind of housing across Europe (Bamford 2005;Droste 2015;Labit 2015), with some notable cases in long-established German intergenerational projects (Labit and Dubost 2016;Borgloh and Westerheide, 2012) as well as in the US (Glass 2013;Glass and Vander Plaats 2013;Markle et al 2015) and Australia (Forbes 2002) and for men as well as women. Mutual support is a significant and highly prized feature of New Ground and the women offered numerous examples of what they termed 'OWCH in action'for example, preparing meals for each other during periods of ill health; driving each other to hospital appointments; organizing visiting rotas for residents in hospital.…”
Section: Mutual Aid Care and Lovementioning
confidence: 99%
“…As commentators of co-housing in general have observed, sharing and mutuality can conflict with the protection of private space (Jarvis, 2015). Co-housing requires learning to manage the conflicts that can result from the messy boundaries between individual and collective life, as well as engaging in forms of informal care alongside formal support (Labit and Dubost, 2016). There is also the risk that such communities are the reserve of the privileged (Blanchard, 2013; LaFond and Tsvetkova, 2017) and the ‘secession of the successful’ (Cashin, 2001; Chiodelli and Baglione, 2014) from the mainstream.…”
Section: Senior Co-housing As a Window On Post-traditional Ageingmentioning
confidence: 99%